Possible Role for Bacteriophages in the Treatment of SARS-CoV-2 Infection - Vijaya Nath Mishra; Nidhi Kumari; Abhishek Pathak; Rajnish Kumar Chaturvedi; Arun Kumar Gupta; Rameshwar Nath Chaurasia (International Journal of Microbiology)
An outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was first reported in Wuhan City, China, in December 2019. Since then, the outbreak has grown into a global pandemic, and neither a vaccine nor a treatment for the disease, termed coronavirus disease 2019 (COVID-19), is currently available. The slow translational progress in the field of research suggests that a large number of studies are urgently required. In this context, this review explores the impact of bacteriophages on SARS-CoV-2, especially concerning phage therapy (PT). Bacteriophages are viruses that infect and kill bacterial cells. Several studies have confirmed that in addition to their antibacterial abilities, bacteriophages also show antiviral and antifungal properties. It has also been shown that PT is effective for building immunity against viral pathogens by reducing the activation of NF kappa B; additionally, phages produce the antiviral protein phagicin. The Ganges river in India, which originates from the Himalayan range, is known to harbor a large number of bacteriophages, which are released into the river gradually by the melting permafrost. Water from this river has traditionally been considered a therapeutic agent for several diseases. In this review, we hypothesize that the Ganges river may play a therapeutic role in the treatment of COVID-19.